Analisis Ijārah, Wadī’ah dan Maslahah terhadap Transaksi Penyimpanan Darah Tali Pusat Bayi di Rumah Sakit Mitra Keluarga Darmo Satelit Surabaya - Holis Holis (Maliyah : Jurnal Hukum Bisnis Islam, 2021)
This research is field research that discusses the transaction of storing a baby's umbilical cord blood that occurs at the Darmo Satelit-Surabaya "Mitra Keluarga" Hospital in the theoretical perspective of maslahah (benefits), Ijārah (lease) and Wadī'ah (savings). This study proposes two problem formulations, namely: first, a description of the baby's umbilical cord blood storage transactions that occurred at the Darmo Satelit-Surabaya "Mitra Keluarga" Hospital. Two, analysis of maslahah, Ijārah, and Wadī'ah on transactions for storing baby's umbilical cord blood at the Darmo Satelit-Surabaya "Mitra Keluarga" Hospital. The results of the study concluded that the hospital stores umbilical cord blood that has been cut and stored through stem cell transplantation and cell therapy. From the perspective of Ijārah, Wadī'ah, and maslahah, the practice is permissible because there is no element of garār and gives maslahah for human life.